Meritocracy and inequality in the climate debate in Edinburgh, Scotland - Hunjan, Nia; Gay-Antaki, Miriam (Frontiers in Climate, 2024)
This paper underscores the role that structural barriers play in climate change research in Edinburgh, Scotland. By employing an intersectional gender analysis we stress how unequal power relations underly our understanding of climate change, influence the quality and nature of climate research and responses developed. Using semi-structured and unstructured interviews with women and men working in climate change, we identify the shared experiences of individuals who face gendered barriers in climate science and policy, examine their perception of privilege, and their consequent perceived success in climate change research. Our findings stress the relationship between the concept of meritocracy, the underrepresentation of women and marginalized groups in science, and the reproduction of systematic barriers to contribute to the climate debate. We stress the importance of relationships and networks in supporting and encouraging marginalized voices to succeed in participating in climate change research and science more broadly.